The Extent to which the Principles of Constructivist Theory are Represented in Biology Textbooks of the Ninth and Tenth Grades in Jordan: An Analytical Study - Zaitoon, Esra'a Hanafi; Majali, Mohammed Da'od (Journal of Educational and Psychological Sciences, 2022)
This study aimed at identifying the extent to which the principles of constructive theory are represented in the biology textbooks of the ninth and tenth grades in Jordan. The analytical descriptive approach was employed. The instrument of the study consisted of six domains, which in turn include (23) sub-principles. The validity and reliability of the instrument was verified. The Chi- square (x²) was used to determine whether there is a significant difference(s) between the expected frequencies and the observed frequencies in the biology textbooks for the ninth and tenth grades. The study results revealed that the third domain: "learning based on development paths that enable students to feel the surrounding environment" came at the first rank in the textbooks of biology for the ninth and tenth grades, whereas the fifth domain: "the learner builds the meaning of what s/he learns her/himself, came at the last rank. Moreover, results indicated that there are no statistically significant differences in the representation of the constructive theory-principles between Bilogy textbooks of the ninth and tenth grades, except for the principle of "learning based on development paths that enable students to feel the surrounding environment", where there was a statistically significant difference in favor of the the tenth grade textbook. The study suggests a number of recommendations, among which are the need to increase the representation of some of the principles of constructive theory in the books of biology for ninth and tenth grades in Jordan.